Management system ISO 9001-2015: techniques and tools of quality engineering for the implementation - Cruz-Medina, Fanny Liliana; López-Díaz, Andrea del Pilar; Ruiz-Cardenas, Consuelo (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2017)
This article shows an evolution of quality management system according to the existing regulations in search process improvement, as well as the ISO 9000 standards impact on continuous improvement of organizations by optimizing the products offered to the final consumer. Similarly analysis and quality engineering makes the necessary inputs in the generation of technical and implementation methods for monitoring and control based on statistics and mathematical models useful for cost reduction, reduction of time and quality improvement processes lives of employees, finally a interrelate with the requirements of ISO 9001:2015 that is standard and tools from the perspective of quality engineering could be applied to ensure the success and sustainability of a system is carried out Quality Management in an organization either goods or services.